2012
DOI: 10.1556/ceugeol.55.2012.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Porosity and compatibility of repair mortars and Hungarian porous limestones

Abstract: Porosity and water absorption of different binder/aggregate ratios of repair mortar and porous limestone were studied that were used in many Hungarian monuments. Different types of mortars were analyzed by using mercury intrusion porosimetry (MIP) and the water saturation method (WSM). Test results showed that there was a strong correlation between the absorption mechanism and the porosimetric characteristics. Mechanical properties of the tested mortars were observed earlier. Pore size distribution confirms th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…In this line, the calcarenites cemented by smaller calcite grains and with higher pore size (BC-Y1 and BC-Y2) exhibit greater strength reductions due to water saturation than the varieties cemented by greater calcite grains and with lower pore diameters (BC-BL, BC-BG and BC-DM). These results are in agreement with those found by Török [49], Papay and Török [50] and Török and Szemerey-Kiss [51], [52], who observed that the limestones cemented by fine grained micrite calcite are more water sensitive in terms of strength and durability than those cemented by micro-sparitic calcite. In addition, they also found the existence of a close relationship between the pore structures and the mechanical properties of Hungarian limestones.…”
Section: Variation Of Mechanical Properties Due To Water Saturationsupporting
confidence: 92%
“…In this line, the calcarenites cemented by smaller calcite grains and with higher pore size (BC-Y1 and BC-Y2) exhibit greater strength reductions due to water saturation than the varieties cemented by greater calcite grains and with lower pore diameters (BC-BL, BC-BG and BC-DM). These results are in agreement with those found by Török [49], Papay and Török [50] and Török and Szemerey-Kiss [51], [52], who observed that the limestones cemented by fine grained micrite calcite are more water sensitive in terms of strength and durability than those cemented by micro-sparitic calcite. In addition, they also found the existence of a close relationship between the pore structures and the mechanical properties of Hungarian limestones.…”
Section: Variation Of Mechanical Properties Due To Water Saturationsupporting
confidence: 92%
“…2). The textural properties of these limestone types have been described in previous works (Török 2003, Pápay and Török 2010, Szemerey-Kiss and Török 2012. These limestone/mortar samples were also prepared in stainless steel casts.…”
Section: Sample Preparationmentioning
confidence: 99%
“…When attempting to escape the masonry, the water would commonly escape through the mortar joint, the stone, or the brick. A high capillarity causes moisture to pass in greater volume that can cause moisture retention, putting the masonry at a more susceptible state that encourages salt formations and problematic freeze/thaw issues [17]. Therefore, mortars/substrate compatibility criteria are always related to physical parameters, such as porosity and hydric properties.…”
Section: Introductionmentioning
confidence: 99%